Questioning the Entrepreneurial State Status-quo, Pitfalls, and the Need for Credible Innovation Policy - Wennberg, Karl; Sandström, Christian (International Studies in Entrepreneurship,, 2022)
The 2008 financial crisis and the COVID-19 pandemic have made the authorities to increasingly turn inward and use ethnocentrism, protectionism, and top-down approaches to guide policy on trade, competition, and industrial development. The continuing aftereffects of such policies range from the rise and seeming success of authoritarian states, rise of populist and protectionist trends, and evolving academic agendas inspiring the reemergence of top-down industrial policies across the world. This open access edited volume contains contributions from 40 scholars with expertise in economics, innovation, management, and economic history. The chapters offer unique theoretical and empirical contributions discussing topics such as how industrial policies affect risk, incentives, and information for investments. They also address the policy perspectives on new technologies such as AI and its implications for market entry, the role for independent entrepreneurship in increasingly regulated markets, and whether governments should focus on market interventions or institutional capacity-building. Questioning the Entrepreneurial State initiates a much sought-after debate on the notion of an Entrepreneurial State. It discusses the dangers of top-down approaches to industrial policy, examines lessons from such approaches for future policy design, and calls attention to the progress of open and contestable markets in a sound economy and society. .